An efficient method for audio watermarking using SWT and mean value quantization - Mushgil, Baydaa Mohammad (2016)
Digital watermarking has been capturing the interests in programming society several decades ago due to the development of software and programming techniques that cause an increase in illegal use of digital files. In addition, with the widespread use of Internet which support sharing any digital files easily, this had simplified distribution of illegal digital files without the owner’s permission. As the multimedia files; which include images, audio, and video clips; are prone to piracy, the multimedia industry and owner’s of digital media are coping with this issue to protect their intellectual property. Furthermore, the multimedia digital market needs to find solutions for copyright protection. A robust, imperceptible and high capacity algorithm is proposed by using the stationary wavelet transform and the quantization index modulation technique with new synchronization method. The results obtained show high robustness towards signal processing and manipulating attacks specially the de-synchronization attacks such as jittering, cropping, and zero inserting attacks. In addition, the imperceptibility and capacity obtained are considered high with respect to signal to noise values. A subjective test with volunteer’s listeners had been conducted for the proposed method. The findings show high imperceptibility with subject difference grade SDG of 4.76; meanwhile high payload capacity with mean value of 176.4 bps is achieved. Hence, based on these results, the proposed audio watermarking method outperforms most of the previous studies